COMPARISON OF K-TYPE AND T-TYPE THERMOCOUPLES FOR STABILITY AND UNIFORMITY OF INFANT INCUBATOR TEMPERATURE TESTING BASED ON IEC 60601-2-19 - Nurdina Gita Pratiwi; Siddiq Wahyu Hidayat; Wuwus Ardiatna; Chery Chaen Putri (JURNAL STANDARDISASI, 2019)
Infant incubator is one of the most important medical devices for newborn survival, especially preterm. However, aside from its benefits, some irregularities can be found on the devices that could lead to infant mortality, such as temperature deviations. The problem can be minimized by testing the infant incubator temperature parameter in accordance with IEC 60601-2-19 standard. However, there are various types of temperature sensors for related tests. Therefore K-Type and T-Type Thermocouples are compared in order to provide recommendations for infant incubator testing. The measurement technique used were referred to the instructions stated in IEC 60601-2-19 sub-clause Stability (with tolerance ±0.5oC) and sub-clause Uniformity (with tolerance ±0.8oC). For K-type thermocouples, the highest stability results at 32oC is -0.2oC and at 36oC is -0.4oC, while the highest uniformity results at 32oC is -0.1oC and at 36oC is -1.6oC, with the uncertainty of 1.7oC. For T-type thermocouples, the highest stability results at 32oC is 0.4oC and at 36oC is -0.4oC, while the highest uniformity results at 32oC is 0.7oC and at 36oC is 0.8oC, with the uncertainty of 0.3oC. The results of the independent t-test showed a different average, where the T-type thermocouples was higher than the K-type thermocouples. In other words, T-type thermocouples could be recommended for infant incubators testing.